Advanced numerical modelling of light-gauge steel framed walls subject to eccentric compression. (1st April 2022) - Peiris, Mithum; Mahendran, Mahen
Highlights: Investigated the effects of geometric imperfections on the capacities and failure modes of eccentrically loaded studs. Used simple single stud FE models to investigate the behaviour of sheathed LSF walls under eccentric compression. Developed an advanced FE model for LSF wall panels by including sheathing, tracks and screw connections. Validated the advanced model through comparison of failure modes, capacities and load-displacement curves from experiments. Highlighted the benefits of using advanced numerical modelling over basic single stud modelling for LSF walls. Abstract: The current numerical studies and design of light-gauge steel framed (LSF) wall and floor systems are largely confined to individual members with idealised boundary conditions. Idealised single stud models of LSF walls that have been extensively used in the past are unable to capture the complex behaviour associated with stud-to-sheathing and stud-to-track connections. The ultimate capacities and failure modes predicted by these models may not always be accurate because of which designers have to resort to expensive and time-consuming full-scale testing. Advanced numerical models that explicitly model all LSF wall components are available in recent literature. However, they are limited to LSF walls under axial compression. In this study, the behaviour of LSF walls made of lipped channel studs under eccentric axial compression was investigated by developing a sheathed stud model simulating the sheathing material, tracks and connections using ABAQUS. This advanced model incorporated material and geometrical non-linearities, contact interactions, non-linear behaviour of stud-to-sheathing connections and explicit modelling of gypsum plasterboard sheathing, and was validated using experimental results. The failure modes, ultimate capacities and load versus axial shortening and lateral deflection curves predicted by the advanced model were compared with those predicted by the simple single stud models and suitable recommendations were proposed for finite element modelling of LSF walls under combined loading actions. This paper presents the details of the development of advanced models of LSF walls subject to compression and bending actions and its findings.